2013
DOI: 10.1111/jdv.12224
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes: an update on its role in the pathogenesis of acne

Abstract: In recent years, significant progress has been made in the understanding of the pathophysiological mechanisms of acne and the role of Propionibacterium acnes. With this review, the authors aim to provide an update on the current understanding of the role of P. acnes in the development of acne lesions and analysing the potential implications for future treatments. A total of 188 articles published between January 1980 and March 2013 were searched using key words such as acne, P. acnes, microbiology, Corynebacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
168
0
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(186 citation statements)
references
References 77 publications
2
168
0
16
Order By: Relevance
“…Especially, P. acnes is regarded as a causative bacterium involved in the pathogenesis and exacerbation of acne vulgaris (Gollnick et al, 2003;Beylot et al, 2014). Moreover, it has been reported that P. acnes was simultaneously isolated with staphylococci in severe acne patients (Nishijima et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, P. acnes is regarded as a causative bacterium involved in the pathogenesis and exacerbation of acne vulgaris (Gollnick et al, 2003;Beylot et al, 2014). Moreover, it has been reported that P. acnes was simultaneously isolated with staphylococci in severe acne patients (Nishijima et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical picture is manifested by seborrhoea, non-inflammatory comedones (blackheads and whiteheads), inflammatory papules, pustules or nodules and scarring, which originate from the pilosebaceous units (Strauss et al, 2007;Thiboutot et al, 2009;Nast et al, 2012). The pathogenesis of acne is multifactorial and includes increased sebum production by androgen-mediated hyperactive sebaceous gland, follicular hyperkeratinization, bacterial colonization by Propionibacterium acnes, a common anaerobic Grampositive commensal of normal skin and release of inflammatory mediators (Contassot et al, 2014;Beylot et al, 2014). Multiple acne therapies are available depending on the severity, type and extent of acne lesions and topical retinoids, antimicrobials and benzoyl peroxide, oral antimicrobials and oral isotretinoin (retinoid) (Strauss et al, 2007;Thiboutot et al, 2009;Nast et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…38 Propionibacterium acnes (P. acnes) has been identified in acne lesions and plays, together with the sebaceous gland, an important role in the pathogenesis of the condition: P. acnes, in fact, secretes lipases, chemotactic factors, metalloproteases and porphyrins, inducing an inflammatory response, with production of free radicals, and causing keratinocyte damage. 39 …”
Section: Acne and The Inflammatory Role Of P Acnesmentioning
confidence: 99%
“…The organism catabolizes sebaceous triglycerides, using the glycerol moiety as a carbon source without catabolizing the fatty acids. While this species has been advocated to play a fundamental role in the etiogenesis of acne (5,6), a significant controversy remains as to how important a role P. acnes plays (4,7). Recent metagenomic studies have confirmed it to be the major inhabitant of pilosebaceous units (8).…”
mentioning
confidence: 99%